Descriptive Osteology of a Newly Described Stone Loach, Oxynoemacheilus chomanicus (Kamangar et al., 2014) (Cypriniformes, Nemacheilidae) - Parvin Mafakheri; Soheil Eagderi; Amir Qadermarzi (International Journal of Zoology)
Oxynoemacheilus chomanicus is a newly described species of the family Nemacheilidae from the Choman River drainage of the Tigris basin. This study was conducted to provide the detailed osteological characteristics of this species and comparing them with those of other endemic species of the genus Oxynoemacheilus from inland water basins of Iran, namely, kiabii, O. persa, O. brandtii, O. kermanshahensis, and O. bergianus. For this purpose, nine specimens of O. chomanicus were collected, cleaned, and stained for osteological examination. Then, a detailed description of their skeletal structure was provided. The results showed that O. chomanicus can be distinguished from other studied species of the genus Oxynoemacheilus due to possessing an orbital shelf, number of the vertebrae, number of the hypurals, number of the unbranched rays in anal fin, features of the hemal and neural spines, and connection pattern of the parietal and frontal.